Teaching Library: Reference Librarian - PTAR Cawangan Negeri Sembilan, Unit Perkhidmatan Perpustakaan (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA, Negeri Sembilan, 2025)
Teaching Library Project is a collaborative project between Perpustakaan Tun Abdul Razak and Bachelor’s Degree in Information Science (Hons.) Library Management programme, Faculty of Information Science. The project aims to introduce a knowledge sharing concept from the industrial perspective into the P&P sessions, specifically for the course code IML465: Digital Reference Services.